Long-range order in Gibbs lattice classical linear oscillator systems - Skrypnik, W.I. (Український математичний журнал, 2006)
The existence of the ferromagnetic long-range order (lro) is proved for Gibbs classical lattice systems of linear oscillators interacting via a strong polynomial pair nearest neighbor (n-n) ferromagnetic potential and other (nonpair) potentials that are weak if they are not ferromagnetic. A generalized Peierls argument and two different contour bounds are our main tools. Доведено існування феромагнітного далекого порядку для гіббсівської класичної ґраткової системи лінійних осциляторів, що взаємодіють завдяки сильному парному поліноміальному феромагнітному потенціалу близьких сусідів та іншим (непарним) потенціалам, які слабкі, якщо не феромагнітні. При цьому використано узагальнений аргумент Пайєрлса та дві контурні нерівності.